Intestinal Bacterial Communities That Produce Active Estrogen-Like Compounds Enterodiol and Enterolactone in Humans - Clavel, Thomas; Henderson, Gemma; Alpert, Carl-Alfred; Philippe, Catherine; Rigottier-Gois, Lionel; Doré, Joe̊l; Blaut, Michael (Applied and Environmental Microbiology, 2005)
Lignans are dietary diphenolic compounds which require activation by intestinal bacteria to exert possible beneficial health effects. The intestinal ecosystem plays a crucial role in lignan metabolism, but the organisms involved are poorly described. To characterize the bacterial communities responsible for secoisolariciresinol (SECO) activation, i.e., the communities that produce the enterolignans enterodiol (ED) and enterolactone (EL), a study with 24 human subjects was undertaken. SECO activation was detected in all tested fecal samples. The intestinal bacteria involved in ED production were part of the dominant microbiota (6 x 10⁸ CFU g⁻¹), as revealed by most-probable-number enumerations. Conversely, organisms that catalyzed the formation of EL occurred at a mean concentration of approximately 3 x 10⁵ CFU g⁻¹. Women tended to have higher concentrations of both ED- and EL-producing organisms than men. Significantly larger amounts of EL were produced by fecal dilutions from individuals with moderate to high concentrations of EL-producing bacteria. Two organisms able to demethylate and dehydroxylate SECO were isolated from human feces. Based on 16S rRNA gene sequence analyses, they were named Peptostreptococcus productus SECO-Mt75m3 and Eggerthella lenta SECO-Mt75m2. A new 16S rRNA-targeted oligonucleotide probe specific for P. productus and related species was designed and further used in fluorescent in situ hybridization experiments, along with five additional group-specific probes. Significantly higher proportions of P. productus and related species (P = 0.012), as well as bacteria belonging to the Atopobium group (P = 0.035), were typical of individuals with moderate to high concentrations of EL-producing communities.